Romanian claims against Bulgaria during the period of the Balkan Wars - Znamierowska-Rakk, Elżbieta (Balcanica Posnaniensia. Acta et studia, 2012)
This article is to demonstrate the genesis and repercussions of the Romanian territorial claims against Bulgaria during the war period of the 1912-1913 in the Balkan Peninsula. What is most stressed is the direct relationship of the said claims with the separation of Bessarabia from the Romanian state, executed by the 1878 Berlin truce and annexation of Northern Dobrudja, a region inhabited mostly by Bulgarians. This last fact inspired the anxiety in Bucharest, that Bulgaria might claim that land by force. This was worsened after 1908, when Bulgaria proclaimed itself a sovereign empire, intent on incorporating major parts of Macedonia and Thrace since the decisive victory over the Ottoman Turkey. Such broadening of the Bulgarian borders was regarded in Bucharest as a threat to the political equilibrium in the Balkans, endangering the Romanian state security and territorial integrity. As a result the government of Romania issued a claim to reestablish the border with Bulgaria, which was in essence a claim over Southern Dobrudja. In spite of rather favorable international circumstances in the early XX century, the Romanians were unable to bring this notion into being until the second half of 1913, the outbreak of an inter-alliance war, a result of frictions between Bulgaria, Serbia and Greece. The lack of success on the side of the Bulgarian armed forces at the western front and the fact that their northern and northeastern provinces were left unprotected incited Romania to invade Bulgaria and annex the Southern Dobrudja. A Turkish invasion followed shortly. As a consequence, and with recognition of the European superpowers of the time, on 10th August 1913 in Bucharest a harsh treaty was imposed on Bulgarians, with the loss of the contested Southern Dobrudja amongst other terms.